An international systematic review of cyberbullying measurements. (December 2020) - Chun, JongSerl; Lee, Jungup; Kim, Jinyung; Lee, Serim
Abstract: Cyberbullying victimization is an international phenomenon and is increasing globally at a high rate. However, studies have shown inconsistent findings for the definition, measurement, and prevalence of cyberbullying victimization and perpetration. To provide an overview of the existing scales and to suggest ways to standardize the cyberbullying measurement, this study analyzed sixty-four international studies on cyberbullying measurements using the following categories: general characteristics, definition of cyberbullying, study sample characteristics, sample size, type of device or social media, time frame, survey type, item-pooling method, subscales, reliability, and validity. Regarding the definition of cyberbullying, 46 of the 64 studies explained the concept of "cyberbullying." Furthermore, only 15 studies followed the recommended guidelines, either fully or partially, when developing their scale. Although most of the cyberbullying instruments revealed moderate to high reliability, only half of the studies assessed the validity of the cyberbullying measurements, with a high portion of them testing the construct validity. Our findings address the need for a consistent and standardized definition of cyberbullying to use worldwide, which may be the most important factor in measuring cyberbullying behaviors. Highlights: Approximately 71.9% of the studies explained the concept of "cyberbullying". Half used the word "cyberbullying", but the other half used alternative words. Only 15 studies (23.4%) followed the recommended guidelines for the scale development. Only half assessed the validity of the cyberbullying measurement tools. Findings address the need for a consistent and standardized definition.